THE EFFECT OF PRODUCT INNOVATION AND CUSTOMER ENGAGEMENT ON REPURCHASE INTENTION THROUGH BRAND TRUST MEDIATION OF HIJAB PRODUCTS IN THE TIKTOKSHOP - Oktaviani Putri Dita Arumsari; Ery Tri Djatmika; Agus Hermawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine the influence of product innovation and customer engagement on repurchase intention of hijab products in TikTok Shop with brand trust as a mediating variable. The research method uses a quantitative approach with causal research design. The research sample consisted of 228 female employees of PT Pabrik Kertas Tjiwi Kimia who actively shop at TikTok Shop. Data were collected through a Likert-based questionnaire, then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that product innovation (β = 0.366; p < 0.001) and customer engagement (β = 0.385; p < 0.001) had a significant positive effect on repurchase intention. Both also had a significant effect on brand trust, which in turn had a strong influence on repurchase intention (β = 0.421; p < 0.001). A mediation test demonstrated that brand trust mediated the relationship between product innovation (β = 0.091; p = 0.013) and customer engagement (β = 0.162; p = 0.007) and repurchase intention. This finding indicates that product innovation and consumer engagement need to be integrated with a brand trust-building strategy to increase loyalty and repurchase intention among hijab consumers on the TikTok Shop platform.